Product Quality and Price on the Purchase Decision of Hawai Bakery Agents Merauke Products - Nurul Fadilah Aswar; Muhammad Kadafi Burhanuddin; Ifah Finatry Latiep (Economics and Digital Business Review, 2020)
This study aims to determine the effect of product quality on consumer purchasing decisions at Merauke Hawaiian Bread Agent outlets. (2) To determine the effect of price on consumer purchasing decisions at Merauke Hawai Bread Agent outlets. (3) To determine product quality and price have a joint influence on consumer purchasing decisions at Hawai Bakery Agent outlets in Merauke. The approach taken in this study using a quantitative research approach and the population in this study was 4,757 people with a study sample of 94 people. The results showed that product quality partially has a positive and significant effect on purchasing decisions, price partially has a positive and significant effect on purchasing decisions. Simultaneously, the variables of product quality and price have a positive and significant effect on purchasing decisions.